Murādif dan Musytarak: Analisis Ambiguitas Semantik dan Implikasinya terhadap Variasi Interpretasi Hukum Islam. - Habibi H (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2026)
Differences in Islamic legal fatwas are commonly associated with varying methods of ijtihād, although legal interpretation begins with determining the meaning of legal texts. This study examines the influence of murādif (near-synonymy) and musytarak (lexical polysemy) on legal interpretation and explains the role of tarjīḥ in resolving semantic ambiguity. Using normative legal research with conceptual and uṣūl al-fiqh approaches, this study applies a descriptive-analytical method based on library research. The findings reveal that murādif and musytarak create multiple interpretive possibilities, while tarjīḥ functions as the methodological mechanism for selecting the strongest meaning according to the principles of uṣūl al-fiqh. Consequently, differences in fatwas should be understood as the result of a systematic interpretive process rather than contradictions within Islamic legal sources.